Special Issue on 13th International Society of Asphalt Pavements (ISAP) Conference - Soares, Jorge Barbosa; Tebaldi, Gabriele; Aragão, Francisco Thiago Sacramento; Savasini, Kamilla Vasconcelos; Romeo, Elena; Dave, Eshan (Transportes, 2020)
The International Society for Asphalt Pavements (ISAP) is a volunteer organization of professionals and experts in asphalt engineering whose goal is to share the latest in leading edge asphalt pavement technology worldwide. ISAP’s most important event, its Conference, is held every four years and the 13th ISAP Conference on Asphalt Pavements (ISAP2018) took place in Fortaleza (Brazil) from June 19th to 21st 2018, for the first time in Latin America. There were participants from 25 countries presenting and debating ideas covering a wide range of topics within pavement infrastructure. Such events provide opportunities to share and learn ideas and discuss how to transform the best available knowledge into applications that can enhance people’s lives, respecting the environment with an eye on future generations. ISAP promotes such diverse gatherings and helps building a creative environment to keep turning the wheel of knowledge. [...]